ФИЗИКА ТАЪЛИМИДА ТИЗИМЛИ ЁНДАШУВ УСУЛИНИ ҚЎЛЛАШ САМАРАДОРЛИГИ - Рўзиева, Д.С. (SCIENCE and SOCIETY, 2021)
The article gives an idea of the possibilities and effectiveness of the organization of a systematic method of teaching physics in Higher Educational Institutions of technical orientation.
Keywords: system approach; system principles; professional competence; modeling; information environment